Mass rearing of platynopus melachantus BOISDUVAL (HEMIPTERA: PENTATOMIDAE) - Mohamad Harris Nasir; Muhammad Hafiz Aiman; Wollis, Lester; Mohanaraj Sithampalanadanarajah; Mathews, Joshua (Penerbit Universiti Kebangsaan Malaysia, 2024)
The mass rearing of predator insects for biological control in agricultural areas, such as oil palm has gained significant interest as a sustainable approach for pest management. This research focuses on evaluating the mass rearing system and biological characteristics of Platynopus melachantus Boisduval, a potential biological control agent for leaf-eating pests. Result of this study revealed that the P. melachantus has a high fecundity rate of 133.25±32.92 eggs/female, making it a promising candidate for mass-rearing programs. High percentage of egg hatching (84.81±2.45%) and moderate survival rate of nymphs to become an adult (56.08±3.64%) demonstrate the success of the rearing process. Results also documents the developmental stages and lifespan of P. melachantus, with a total lifecycle duration of 122.48±10.53 days and five instar stages. This study highlights the effectiveness of T. molitor larvae as a suitable diet for the mass rearing of predator insects. This study suggested the utilization of Tenebrio molitor larvae and pupae as the primary food source is possible in controlled laboratory environment.